Prevalence of systemic lupus erythematosus in Spain: higher than previously reported in other countries? - Cortés Verdú, Raúl; Pego-Reigosa, José M; Seoane-Mato, Daniel; Morcillo Valle, Mercedes; Palma Sánchez, Deseada; Moreno Martínez, María J; Mayor González, Marta; Atxotegi Sáenz de Buruaga, Joana; Urionagüena Onaindia, Irati; Blanco Cáceres, Boris A; Silva-Fernández, Lucía; Sivera, Francisca; et al. (Rheumatology (Oxford, England), 2020)
Abstract Objectives Prevalence of SLE varies among studies, being influenced by study design, geographical area and ethnicity. Data about the prevalence of SLE in Spain are scarce. In the EPISER2016 study, promoted by the Spanish Society of Rheumatology, the prevalence estimate of SLE in the general adult population in Spain has been updated and its association with sociodemographic, anthropometric and lifestyle variables has been explored. Methods Population-based multicentre cross-sectional study, with multistage stratified and cluster random sampling. Participants were contacted by telephone to carry out a questionnaire for the screening of SLE. Investigating rheumatologists evaluated positive results (review of medical records and/or telephone interview, with medical visit if needed) to confirm the diagnosis. To calculate the prevalence and its 95% CI, the sample design was taken into account and weighing was calculated considering age, sex and geographic origin. Multivariate logistic regression models were defined to analyse which sociodemographic, anthropometric and lifestyle variables included in the telephone questionnaire were associated with the presence of SLE. Results 4916 subjects aged 20 years or over were included. 16.52% (812/4916) had a positive screening result for SLE. 12 cases of SLE were detected. The estimated prevalence was 0.21% (95% CI: 0.11, 0.40). SLE was more prevalent in the rural municipalities, with an odds ratio (OR) = 4.041 (95% CI: 1.216, 13.424). Conclusion The estimated prevalence of SLE in Spain is higher than that described in most international epidemiological studies, but lower than that observed in ethnic minorities in the United States or the United Kingdom.